PERBEDAAN SOFTSKILL MAHASISWA SEBELUM DAN SESUDAH DIBERIKAN BIMBINGAN KELOMPOK SAAT IMPLEMENTASI KAMPUS MENGAJAR - Ridayanti, Putu Windi; Marleni, Kadek Devy (Pedagogi: Jurnal Ilmiah Pendidikan, 2024)
Students' soft skills are an important thing to have before they complete their studies. This ability cannot be obtained from activities on campus, but can be increasingly discovered when they start doing activities outside the institution. Currently, the Merdeka Belajar Kampus Merdeka, one of which is a teaching campus, has a positive impact on students in improving hard skills and soft skills. The aim of this research is to analyze the differences in students' soft skills before and after being given group guidance. Quantitative research method with a one group pre-post ne group pre-post-test design approach. The sample obtained was 50 students who are currently involved in Kampus Mengajar activities. The sampling technique uses cluster random sampling, with the research instrument in the form of a soft skills questionnaire covering 5 important points of communication skills, critical thinking, teamwork, ethics and morals and leadership abilities. Analysis uses compare mean. The result was that 5 aspects of soft skills had increased before and after being given group guidance, the results were statistically significant with a p value <0.05. The conclusion is that there are differences in the soft skills possessed by teaching campus students when given group guidance.